Muslim revivalism in the contemporary society - Yousif, Ahmad (Legas Publishing, 2012)

(untitled)
For the past few decades, the world has witnessed the emergence of various Islamic revivalist movements which contemporary social scientists and policy makers are trying to understand and rationalize. Many of these movements aim to purify Islam from “un-Godly” elements and return it to its “original” form. Islamic revivalism, whether political, social, or spiritual, has been a re-occurring phenomenon throughout the history of Islam, and has generated great interest among researchers and intellectuals, both in and outside the Muslim world. In recent years, Muslim revivalist groups, particularly in Asia and North Africa, have challenged the political power structures and managed to mobilize great membership. For example, the current “Arab Springs” in the Middle East has managed to change a number of regimes, such as Tunisia, Egypt, Libya, Yemen, and continuing to spread to other countries in the region. In Southeast Asia, the relationship between state and religion has become increasingly interconnected and intertwined, largely due to the pressure of Islamic movements that have attempted to influence the government towards shaping and transforming society in a manner that corresponds to Islamic ideals and values. This has led to increase “Islamic” activities on the part of the government, and to growing concerns by both Muslims and non-Muslim minorities about how far this process will go. This book is written entirely by selected scholars, in the field of Islamic studies, to study such religious movements and to explore the Muslim Revivalism in the Contemporary Society.